The mediation effect of vitamin A and vitamin D supplement in the association between serum vitamin K levels and musculoskeletal disorders in preschool children - Ge, Qiaoyue; Zhang, Lu; Sun, Zeyuan; Cai, Jiarui; Jiang, Xia; Wang, Hong; Li, Xinxi; Yu, Chuan; Xiao, Chenghan; Liu, Zhenmi (Frontiers in Nutrition, 2023)
Introduction: Vitamin K deficiency may elevate the incidence of musculoskeletal disorders (MSD), whereas it lacks validation for pediatric populations and has uncertain dose recommendations. In this context, we hypothesized that serum vitamin K levels are associated with MSD in preschool children, and the widely used vitamin A and vitamin D supplements may mediate these associations based on potential mechanisms, which expects to provide guidance for future practice. Methods: A cross-sectional study was conducted in Chengdu, the major city of southwestern China, from January 2021 to May 2022. Serum levels of vitamin K1/K2 were determined using the high-performance liquid chromatography method, and the diagnosis of MSD was executed by clinicians. A logistic regression model was conducted to assess association between serum vitamin K levels and MSD prevalence, adjusted for confounders. Mediation analysis was further performed and vitamin A and D supplementation was regressed as the mediator. Results: A total of 6368 children aged 0-6 years old were enrolled. MSD was identified in 1179 (18.51%) of the children, while 5189 (81.49%) of them did not present such disorder. After adjusting confounders, a significant difference was found in serum vitamin K1 level between children in MSD and Non-MSD group (OR=0.802, 95%CI 0.745-0.864). No significant difference was found in serum vitamin K2 level between the two groups (OR=0.975, 95%CI 0.753-1.261). The association between vitamin K1 level and MSD prevalence was partly (36.8%) mediated by vitamin A and D supplementation. Conclusions: A low serum vitamin K1 level is connected with an increased risk of MSD among children, highlighting that vitamin A and D supplementation is a helpful intervention to prevent MSD in children with vitamin K deficiency.